Studi Kasus : Intervensi Fisioterapi Pada Kasus Dismenorea Di Universitas Muhammdiyah Surabaya - Swandari, Atik (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: to determine the effectiveness of physiotherapy interventions with warm compresses (hot packs) and abdominal stretching exercises in reducing pain in dysmenorrhea.Methods: This research uses a case study method by providing physiotherapy interventions in the form of warm compresses (hot packs) and abdominal stretching exercises, which are carried out once a day for 2 days. The measuring instrument used is to use a pain scale in the form of the Verbal Discriptive Scale (VDS). Measurements were taken before and after the intervention was given.Results: After 2 days of physiotherapy intervention, the results showed that there was a change in silent pain and motion pain in the patient. Silent pain decreased from a value of 5 to a value of 3 while motion pain decreased from a value of 4 to a value of 1.Conclusion: Physiotherapy interventions in the form of giving warm compresses (hot packs) and abdominal stretching exercises are proven to reduce pain in cases of dysmenorrhea.